Computer assisted orthopaedic surgery: Past, present and future. (October 2019) - Picard, Frederic; Deakin, Angela Helen; Riches, Philip E.; Deep, Kamal; Baines, Joseph
Highlights: Review of background and current state of the art in CAOS using knee arthroplasty as a case study. Evolution of the technology since its inception and the role of industry in orienting the debate in the orthopaedic forum. Industry seems to continue to drive innovation. CAOS technology may have led to some of the recent arthroplasty forum debates such as alignment. Abstract: Computer technology is ubiquitous and relied upon in virtually all professional activities including neurosurgery, which is why it is surprising that it is not the case for orthopaedic surgery with fewer than 5% of surgeons using available computer technology in their procedures. In this review, we explore the evolution and background of Computer Assisted Orthopaedic Surgery (CAOS), delving into the basic principles behind the technology and the changes in the discussion on the subject throughout the years and the impact these discussions had on the field. We found evidence that industry had an important role in driving the discussion at least in knee arthroplasty-a leading field of CAOS-with the ratio between patents and publications increased from approximately 1:10 in 2004 to almost 1:3 in 2014. The adoption of CAOS is largely restrained by economics and ergonomics with sceptics challenging the accuracy and precision of navigation during the early years of CAOS moving to patient functional improvements and long term survivorship. Nevertheless, the future of CAOS remains positive with the prospect of new technologies such as improvements in image-guided surgery, enhanced navigation systems, robotics and artificial intelligence.